2015
DOI: 10.3928/01477447-20150105-07
|View full text |Cite
|
Sign up to set email alerts
|

The Hip-Spine Connection: Understanding Its Importance in the Treatment of Hip Pathology

Abstract: EDUCATIONAL OBJECTIVES As a result of reading this article, physicians should be able to: 1. Discuss the kinematic relationship between the hip and lumbar spine. 2. Explain the innervation of the hip and lumbar spine and how they relate to one another. 3. Recognize the effect of hip disease on the lumbar spine in an athletic population, prior to the onset of degenerative changes. 4. Describe an algorithm for diagnosis and treatment of patients who present with concomitant hip and lumbar spine pain. The hip and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
(16 reference statements)
0
13
0
4
Order By: Relevance
“…In addition to Offierski and Macnab (1983), Yoshimoto et al (2005) reported that alignment abnormalities, such as an increase in sacral slope and enhancement of lumbar lordosis, occur in patients with osteoarthritis of the hip joint. This association is considered to be based on the coordinated movement of the hip joint and lumbar spine and that limitations in one area will affect other areas (Redmond et al 2015). The kinematic function of the SIJ in the lumbopelvic region is not clear.…”
Section: Evaluation Of Degenerative Changes In the Sijmentioning
confidence: 99%
“…In addition to Offierski and Macnab (1983), Yoshimoto et al (2005) reported that alignment abnormalities, such as an increase in sacral slope and enhancement of lumbar lordosis, occur in patients with osteoarthritis of the hip joint. This association is considered to be based on the coordinated movement of the hip joint and lumbar spine and that limitations in one area will affect other areas (Redmond et al 2015). The kinematic function of the SIJ in the lumbopelvic region is not clear.…”
Section: Evaluation Of Degenerative Changes In the Sijmentioning
confidence: 99%
“…Проблема выявления источника боли и определения тактики хирургического или консервативного лечения у пациентов с КВС обсуждается как в зарубежной, так и в отечественной литературе [1,[8][9][10][11]. Неправильная оценка источника жалоб может приводить к ошибкам в выборе тактики хирургического лечения.…”
Section: Discussionunclassified
“…Non-emergency not arthritic hip pain can be further classified as in Table 2 and Table 3 [3]. Reymond proposed hip spine algorithm for clinician to assess patient in systematic manner to avoid unnecessary surgical intervention as in Figure 1 [4]. The algorithm begins with thorough history and physical examination.…”
Section: Discussionmentioning
confidence: 99%